Propofol provides a significant survival advantage in sepsis-associated encephalopathy: A retrospective cohort study investigating one-year all-cause mortality - Li, Yuan; Huang, Han; Shuai, Bingxing (PLOS ONE, 2026)
Introduction Considering the high incidence, mortality, and long-term effects of sepsis-associated encephalopathy (SAE), along with the availability of sedation therapy data and the significance of distress management, this study investigated the relationship between sedation therapy and one-year all-cause mortality in patients with SAE. Methods This retrospective cohort study utilized the Medical Information Market for Intensive Care (MIMIC-IV) database. We gathered demographic data, vital signs, laboratory test results, microbial findings, comorbidities, scoring systems, treatments administered within the first 24 hours of patient admission to the intensive care unit (ICU), and follow-up data from 24 hours after ICU admission to one year. Cox regression models were employed to evaluate the relationship between sedation therapy and one-year all-cause mortality among patients with SAE. Propensity score matching (PSM) and subgroup analyses were used to assess the robustness of the findings. Results Four thousand six hundred eighteen patients with SAE were enrolled, including 3,343 in the sedative group and 1,275 in the non-sedative group; additionally, 511 pairs were matched. A protective correlation was observed between propofol monotherapy and one-year all-cause mortality in patients with SAE, with hazard ratios (HRs) of 0.51 (95% confidence interval (CI), 0.40–0.65), P < 0.001. Furthermore, the interaction between propofol monotherapy and ventilation support significantly increased one-year all-cause mortality, yielding an HR of 0.70 (95% CI, 0.49–1.00) with P for interaction = 0.041. The results of PSM remained robust. Conclusion Our study indicated that compared to patients with SAE who did not receive sedation, administering propofol alone significantly reduced one-year all-cause mortality among patients with SAE. For patients undergoing ventilation support on the first day of ICU admission, the interaction between sedation therapy and ventilation support significantly influenced the one-year all-cause mortality of patients with SAE.